(untitled) (Mustansiria Dental Journal, 2018)
The aim of this study was to compare in vitro the microleakage of a pit and fissure sealant after different enamel surface treatments: (1) acid etching only, (2) air abrasion only, and (3) air abrasion followed by acid etching. Thirty sound human upper premolars were used in this study. The teeth were divided into three groups according to the type of treatment prior to sealant application: Group 1 (in which the occlusal surface was etched with 37% phosphoric acid gel for 30 seconds), Group 2 (in which the occlusal surface was air-abraded for 10 seconds with sodium hydrogen carbonate powder), and Group 3 (in which the occlusal surface was air-abraded as in group 2 and then acid etched as in group 1). Then a light-cured pit and fissure sealant (Fisseal, Promedica, Germany) was applied to the central fissure in the occlusal surface of each tooth and light cured for 20 seconds. Then the teeth were thermocycled between 5ºC and 55ºC for 10 cycles, immersed in 0.5% basic fuchsine dye for 24 hours at room temperature, embedded in auto-polymerizing acrylic resin, sectioned longitudinally bucco-lingually, and examined under a stereomicroscope for dye penetration. The results of this study showed that the highest mean of microleakage scores was in group 2 (air abrasion group), while the lowest mean of microleakage scores was in group 3 (air abrasion + acid etching), with statistically highly significant difference (p<0.01) between group 1 and group 2, and between group 2 and group 3, with statistically non-significant difference between group 1 and group 3 (p>0.05). Air abrasion treatment prior to sealant application was not effective in reducing microleakage and should be followed by acid etching.